2013
DOI: 10.1002/hep.26057
|View full text |Cite
|
Sign up to set email alerts
|

Single determination of C-reactive protein at the time of diagnosis predicts long-term outcome of patients with hepatocellular carcinoma

Abstract: We investigated the prognostic value of C-reactive protein (CRP) in patients with hepatocellular carcinoma (HCC) not amenable to surgery. A total of 615 patients diagnosed with HCC not amenable to surgery between April 1999 and December 2009 at the Department of Gastroenterology of the Medical Universities of Vienna and Innsbruck were included. We assessed the optimal CRP cutoff by regression spline analysis and tested its impact on median overall survival (OS) by the Kaplan-Meier method, univariate analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 23 publications
5
116
2
Order By: Relevance
“…Prior the second TACE, most patients had Child-Pugh A cirrhosis (n ¼ 69, 62%). Overall, the median number of TACE interventions was 3 (range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The median time interval between the first and second TACE was 42 days (range 26-85).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior the second TACE, most patients had Child-Pugh A cirrhosis (n ¼ 69, 62%). Overall, the median number of TACE interventions was 3 (range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The median time interval between the first and second TACE was 42 days (range 26-85).…”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated 15 that elevated C-reactive protein (CRP) values have a strong prognostic significance for patients with HCC. Thus, CRP values (<1 mg/dL and !1 mg/dL) prior the second TACE were included into statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have showed that the preoperative elevated serum CRP level is an independent and significant predicative indicator of poor prognosis and early recurrence in patients with HCC (Hashimoto et al, 2005;Sieghart et al, 2013). However, SAA is superior to CRP for detecting inflammation resulting from viral infections, kidney transplantation, Crohn's disease, and ulcerative colitis (Yamada, 1999), and therefore SAA is probably more useful for detecting slight elevations in systemic or chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Chronically inflamed liver parenchyma due to various viral infections, deposition of substances such as copper and iron and chronic alcoholism, represents a precancerous environment (16). There is increasing evidence that the role of chronic systemic inflammation may be a significant predictor of outcome in various human malignancies, thus including HCC.…”
Section: Proposed Mechanisms In Role Of Rdw In Hccmentioning
confidence: 99%
“…There is increasing evidence that the role of chronic systemic inflammation may be a significant predictor of outcome in various human malignancies, thus including HCC. Multiple studies showed that elevated values of C reactive protein (CRP) predict survival (16,17) and recurrence (18) in HCC. Neutrophil-lymphocyte ratio (NLR), an easily obtainable inflammatory marker, is also proved to be associated with the prognosis of HCC (19).…”
Section: Proposed Mechanisms In Role Of Rdw In Hccmentioning
confidence: 99%